Pengaruh Suhu Ultrasonikasi terhadap Viskositas Gelatin dari Kulit Ayam - Adella Rizki Amalia; Miftahul Khair (Lembaga Yasin AlSys, 2026)
Gelatin is a protein produced through the partial hydrolysis of collagen and is widely used in the food, pharmaceutical, and cosmetic industries because of its functional properties as a gelling, thickening, and stabilizing agent. Chicken skin has the potential to be developed as an economically valuable alternative source of halal gelatin, but information regarding the effect of ultrasonication temperature on the viscosity of chicken skin gelatin remains limited. This study aimed to evaluate the effect of ultrasonication temperature on the viscosity of gelatin extracted from chicken skin using the Ultrasound-Assisted Extraction (UAE) method. Chicken skin was pretreated using a 2% acetic acid solution and then extracted through ultrasonication at temperatures of 35°C, 45°C, and 55°C for 90 minutes with a material-to-solvent ratio of 1:10 (w/v). The viscosity of the extracted gelatin was measured using an Ostwald viscometer. The results showed that ultrasonication temperature affected the viscosity of chicken skin gelatin. The highest viscosity was obtained at 45°C, namely 3.28 cP, whereas treatments at 35°C and 55°C produced viscosities of 2.36 cP and 1.72 cP, respectively. The increase in viscosity at 45°C indicated that this condition optimized the extraction process without causing excessive degradation of the protein chains. In contrast, ultrasonication at 55°C was presumed to reduce the molecular weight of the gelatin, thereby decreasing its viscosity. This study concluded that an ultrasonication temperature of 45°C was the most suitable condition for producing chicken skin gelatin with better viscosity characteristics. These findings provide a basis for developing a more efficient process for extracting halal gelatin from chicken skin.